Expertise, Trustworthiness, Similarity, Familiarity, Likeability, Product-Match Up of Celebrity Endorsement to Purchase Intention - Afifah, Isti Februari (LSPR Institute of Communication & Business, 2022)
Celebrity endorsement has become popular marketing strategy for the last decade. However, it is not always effective. Sometimes, it brings adverse effect to the brand and product due to wrong selection of celebrity figure. Therefore, this study aimed to investigate variables that related to celebrity endorsement, but have most significant influence to purchase intention. Among others: expertise, trustworthiness, similarity, familiarity, likeability, and product-match. So, it can be used by marketers as an insight. There were 200 respondents involved in this explanatory quantitative study. The findings revealed that all variables have positive influence to purchase intention. However, it is only expertise, trustworthiness, similarity, familiarity, and likeability that have significant influence. It means, product-match up had insignificant influence to purchase intention.